PERNIKAHAN WANITA HAMIL PRESPEKTIF HUKUM ISLAM (Studi Kasus di KUA Kecamatan Lasem Kabupaten Remabng) - Lailatul Maghfiroh; Dwi Ari Kurniawati; Shofiatul Jannah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
From the background of the research, the researcher formulates how the implementation of marriage in the KUA, Lasem District, Rembang Regency, how the factors that cause pregnant women, and how pregnant marriages are carried out from the perspective of Islamic law. The method obtained in this study is the method of observation, interviews, and documentation. The primary sources in this study were interviews at the Office of Religious Affairs (KUA) Lasem District, Rembang Regency and the perpetrators of pregnant women. Secondary sources carried out by researchers were obtained in the form of the Qur'an, Hadith, and books related to this researcher. The result of this study is that the implementation of marriages for pregnant women in KUA, Lasem District, Rembang Regency is the same as the implementation of marriages in general. Factors for pregnant women out of wedlock in Lasem District, Rembang Regency, namely promiscuity in the cafe environment where they work, lack of parental attention. Marriage of pregnant women from the perspective of Islamic law, namely that there are fiqh experts who think it is legal and some are invalid, according to the Compilation of Islamic Law, pregnant women can be married but those who marry are men who get pregnant (Article 53 KHI)